Origin of high room temperature ferromagnetic moment of nanocrystalline multiferroic BiFeO3 - Vijayanand, S.; Potdar, H. S.; Joy, Pattayil Alias (Applied Physics Letters, 2009)
Single phase nanocrystalline BiFeO3 of average crystallite size similar to 25 nm with very high magnetization at room temperature is synthesized by an autocombustion method. Magnetic measurements above room temperature show deviation between field cooled and zero field cooled magnetization below 645 K, the Neel temperature (T-N) of the bulk material, indicating intrinsic nature of ferromagnetism. However, observation of a broad magnetic transition above T-N of BiFeO3 and extended up to 800 K suggests the presence of Fe3O4 as a possible magnetic impurity phase. Evidence for the presence of Fe3O4 is obtained from detailed analysis of the powder x-ray diffraction pattern.
Keywords: bismuth compounds; Combustion synthesis; crystallites; ferromagnetic materials; high-temperature effects; magnetic impurities; Magnetic moments; Magnetisation; Multiferroics; Nanostructured materials; Neel temperature; X-ray diffraction